A Rare Case of Nonsyndromic Generalized Radiculomegaly with a Literature Review - Mohammad Al-Obaida (Case Reports in Dentistry)
Radiculomegaly is a rare condition involving elongated tooth roots. This condition has significant clinical implications and has been associated with syndromes such as oculofaciocardiodental syndrome. However, only a few nonsyndromic cases of radiculomegaly have been reported. Here, we report a case of nonsyndromic radiculomegaly in a Saudi individual. A subsequent review of the literature suggests endodontic management modalities for individuals with the dental findings demonstrated in the present case.